Compressive Strength Characteristics of Lightweight Concrete with Modified EPS and Pumice Sand - Munawwar M Nur; Kusnadi Kusnadi; Ichsan Rauf (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
The environmentally friendly lightweight material is a concept for developing construction material technology. One way is to reduce density by using plastic waste such as Expanded Polystyrene (EPS) as the concrete aggregate. Although on the other hand, the mechanical value has decreased significantly. This research explains the development of lightweight concrete, EPS (BREA), which uses Modified EPS waste as coarse aggregate and pumice sand as fine material, obtained locally from Tidore Island. The mixture composition used in this study was 1 Cement: 2 Sand: 3 MEPS, where the compressive strength test was carried out to see its mechanical behaviour. The research shows that the composition above reduces the volume weight and compressive strength values by 56.12% and 78.46%, respectively, compared to normal concrete.